Empowerment of urban agriculture community program’s participants in the Klang Valley, Malaysia - Nazuri, Nur Shuhamin (2021)
In Malaysia, Urban Agriculture program’s initiative has brought local communities together to grow their own food in designated areas and at the same time to empower the community (Bernama, 2020). According to Strzelecka et al. (2017) participation is important in strengthening community empowerment. However, lack of participation among UA community resulted investment and initiative done by government to waste. This study aims to identify dimension of participation (planning, implementation and evaluation) level of Urban Agriculture (UA) program’s respondents towards economic and social empowerment independently, where their effect is design to be moderated by social capital consisting of bonding, bridging and linking. There are five objectives of this study which are : 1) to describe the socio-demographic characteristics of UA program’s respondents and background of UA activities; 2) to determine the level of participation, social capital and empowerment of UA program’s respondents; 3) to investigate the relationship between participation and empowerment of UA program’s respondents; 4) to investigate the relationship between social capital and empowerment of UA program’s respondents; 5) to determine the moderating effect of social capital in the relationship between participation and empowerment of UA program’s respondents. This study recorded majority of the respondents were male, aged between 41-60 years old, married and has obtained secondary school/vocational. Majority of them are also either self-employed or retired with family members of 5-12. Furthermore, Klang Valley UA programs respondents’ level were found to be moderate (planning, implementation, evaluation, bonding, bridging, linking, social empowerment and economic empowerment). Addition to that, relationship between participation, social capital towards empowerment among respondents were found to be insignificant. Hence, resulting social capital (bonding, bridging and linking) do not have moderator function on participation to empowerment. This study has three main contributions. First, it contributes to the body of knowledge as there are not many studies conducted in the field empowerment theory in the perspective of UA program. Second, it contributes to the practice by exploring factors might influence empowerment of UA program’s respondents. Third, it contributes to the policy by assisting concern parties to establish policy to boost the efficiency of the program. The instrument for this study was developed on the basis of literature review, adopt and adapt technique and subsequently improved through pilot test. Through multi- stage random sampling, total of 212 respondents were selected to represents 14 communities from seven districts namely Sri Muda, Batu Tiga, Semenyih, Dengkil, Templer, Kota Damansara, and Batu Caves. The data collection employed a structured self-administered questionnaire through a survey method. The collected data were analyzed using selected analysis procedure through SPSS software and PLS-SEM. Referring to the results, the researcher found that level of social capital, participation and empowerment dimension of UA program’s respondents were at moderate level. For the direct relationship, social capital and participation indicated non-significant relationship with empowerment. On top of that, the interaction between participation and social capital was found to be insignificant to the empowerment. This study put forward numbers of recommendation. Firstly, is to empower the role of community leaders; secondly, to conduct courses and workshop and thirdly; to empower agriculture extension officers. Several recommendations for future studies were discussed. First, other new variable should be examined and future research will consider using qualitative methods to conduct in-depth discussions in order to identify any additional variables with the potential to influence empowerment of UA program’s respondents. Secondly, future studies should consider in looking factors effecting of weak networking social capital, and the aspects of strengthening participation of UA program’s respondents. Thirdly, other possible factors that possibly influence the empowerment of UA program’s respondents should be investigate. It is anticipated that findings can be used as a basis for the future research related to UA program in Malaysia.